Model Pembelajaran Radec: Persepsi dan Implementasi bagi Calon Guru Sekolah Dasar - Mia Komariah; Udin Syaefudin Sa’ud; Wahyu Sopandi; Atep Sujana (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2023)
This study aims to determine the perceptions of prospective elementary school teaching students who have directly experienced applying the RADEC model in learning. The approach used is qualitative with the case study method. Data collection was carried out by interviewing five respondents who were taken randomly from 39 students. Then, data analysis was carried out, namely data reduction, data presentation, describing, and verifying conclusions. Then, data verification is done through peer debriefing. Based on the perceptions and implementation carried out on prospective elementary school teacher students, the RADEC model is a learning model that can help improve understanding of the material, collaborate, and encourage creativity through doing work. Then, based on students' experiences, they desire to apply the RADEC model in teaching elementary schools.